Zoning of the land use conﬂict in the protection areas of the drain network of Páez river basin, Cartago, Costa Rica. - Alfaro-Jiménez, Kevin (Revista Geográfica de América Central., 2019)
This study presents a zoning of land use conflicts in protection areas (AP) of drainages of the Páez river basin. The zoning was delimited and quantified through spatial analysis processes, based on the level curves (1: 10 000) and the digitization of orthophotos. Resulting 59% of the total of AP (7,397 km2) which have a land use conflict. The zoning area with land use conflicts (4,374 km2) was distributed: an 4% in category I (permanent crop), an 81% in category II (agricultural and crops) and finally an 16% in category III (housing, infrastructure and others). The conflict generated by crops and smaller scale by the agricultural use predominate in the degradation of the AP functions at the basin. Confirming the anterior information, the index of land use conflicts (GC) proposed by Danza and Sanabria (2008) resulted in -0.13, evidencing a high affectation in the AP due to inadequate land use. The sub-basins 3, 4, 5, 6, 14 y 20 indicates a major conflict, therefore, mitigation measures should be a priority in this spatial area.